Description of Husband's Knowledge and Support for the Use of Contraception - Dewarawati P; Tenny Tarnoto; Darmawati; Swarjana, I Kadek Dwi (Journal Kiara : Nursing and Midwifery, 2025)
Choosing a contraceptive is one of the important decisions that a married couple must take. However, often this decision does not fully involve the husband, which can result in problems in communication and cooperation between the couple. In many cases, husbands are the main decision-makers, so their understanding and attitudes towards contraception greatly influence family decisions. Therefore, husbands usually have a dominant role in family decision-making, including in reproductive health matters. Research Objectives: To understand the description of husbands' knowledge and support for the use of contraceptives. This research method is quantitative research with an analytical descriptive research design. The sample in this study was 50 respondents according to the inclusion criteria. The sampling technique in this research uses a non-probability sampling method with a proportional sampling technique. The instrument used in this research uses a questionnaire sheet taken from (Noaritasari, 2018). This research uses SPSS Test Analysis. The results and analysis of the research showed that 47 people had presentations (94%). The level of knowledge was poor, and 3 people had sufficient knowledge with presentations (6%). Meanwhile, 30 people showed support from their husbands with presentations (60%), and 20 people did not support them with presentations (40%). So it can be concluded that husbands on average have less knowledge and do not support the use of contraception